2
$\begingroup$

A line $r$ contains the points $A,B,C,D$ in this order. Let $P\notin r$ such that $$\angle APB=\angle CPD$$ Denote furthermore by $G$ the intersection of the angle bisector of $\angle APD$ and $r$.

Prove that $$\frac{1}{GA}+\frac{1}{GC}=\frac{1}{GB}+\frac{1}{GD}$$

My attempt so far:

Let $\Delta APD$ be a triangle, then $PB$ and $PC$ are isogonal lines. Hence $$\frac{AB}{BD}·\frac{AC}{CD}=\Bigl(\frac{AG}{GD}\Bigr)^2$$ (This fact might be proven with the Sine Law)

I don't know how to proceed now...

$\endgroup$
1
$\begingroup$

Let $(XYZ)$ be area of triangle $XYZ$. We have $$(AGP) = (ABP)+(BGP)$$ so

$${ab\sin \alpha\over 2}+{bg\sin \phi \over 2}={ag\sin (\alpha+\phi)\over 2}\;\;\;\;(*)$$

Law of sin for $AGP$ and $BGP$: $$ a= {AG \sin \beta \over \sin (\alpha+\phi)}\;\;\;{\rm and}\;\;\;\;b= {BG \sin \beta \over \sin (\phi)}$$

If we plug this $a$ and $b$ in to $(*)$ and rearrange we get: $${\sin \alpha \sin \beta \over g\sin \phi \sin (\alpha+\phi)} = {1\over BG}-{1\over AG}$$

The same is true for the "right side of picture" and we are done.

enter image description here

$\endgroup$
1
$\begingroup$

Projective solution:

Let perpendicular line to $PG$ through $P$ cuts $AB$ at $T$. Then $T,A,G,D$ are harmonic and $T,B,G,C$ are harmonic, so $${\vec{TB}\over \vec{BG}}: {\vec{TC}\over \vec{CG}} = -1 ={\vec{TA}\over \vec{AG}}:{\vec{TD}\over \vec{DG}}$$

and after some algebraic manipulation we get the desired equation.

$\endgroup$
1
$\begingroup$

Consider an inversion $I_G$ with center $G$ an arbitary radius $R>0$. For every point of the plane $X$ denote $I_G(X)$ as $X'$. Note that $A', B', C', D'$ will lie in order $B', A', D', C'$ on the line $r$.

Before inversion we have $\angle GPB=\angle GPC$ and $\angle GPA=\angle GPD$. Therefore, after inversion we will have $\angle GB'P'=\angle GC'P'$ and $\angle GA'P'=\angle GD'P'$. Hence, triangles $A'PD'$ and $B'PC'$ will be isosceles (with bases $A'D'$ and $B'C'$, respectively). From this we conclude that midpoints of segments $A'D'$ and $B'C'$ are coincide, so $A'C'=B'D'$ or $GA'+GC'=GB'+GD'$. Now remember that $I_G(A)=A'$, so $GA\cdot GA'=R^2$ or $GA'=\frac{R^2}{GA}$. Analogously, $GB'=\frac{R^2}{GB}$, $GC'=\frac{R^2}{GC}$ and $GD'=\frac{R^2}{GD}$. Hence, $\frac{1}{GA}+\frac{1}{GC}=\frac{1}{GB}+\frac{1}{GD}$, as desired.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.